Lesson Study: What Do Pre-Service Teachers Tell? - Soviyah Soviyah (Universitas Ahmad Dahlan, 2018)
Education topics and talks on pre-service teacher training program and Lesson Study have individually been discussed and appeared in many journals among disciplines. However, the empirical studies on the issue about the connection between them and how they can relate and benefit one another are limited and rarely done. This study aims at investigating pre-service English teachersâ€™ perspectives towards Lesson Study, particularly in terms of their knowledge, experience, and plan for it. This study involved seventeen pre-service teachers (PST) in a teacher education faculty in Indonesia who participated as the research subject. Empirical data were collected through interview and Focus Group Discussion (FGD). Data analysis used a descriptive qualitative method. Results of the study showed that: (1) In terms of knowledge about Lesson Study, all PSTs have good knowledge about Lesson Study. In addition, they also show positive response towards Lesson Study, (2) In terms of experience with Lesson Study, most of the PSTs have had experiences with Lesson Study activities. The experiences mostly occurred when they were being directly involved in Lesson Study activities as students, (3) In terms of the plan to do Lesson Study, the majority of the PSTs are planning to take and do Lesson Study in the future, especially when they become real teachers at schools.Â